Analysis Of Patient Receivables Management With Insurance Providers To Achive Receivables Settlement Targets At Persada Hospital Malang - palupi dewi, wening (Journal of Hospital Management and Services, 2024)
Background: Hospital receivables represent a significant issue impacting public healthcare services directly. They can diminish the quality of healthcare provision, hinder investments in facility development and human resources, and increase the risks of payment failures and financial losses for hospitals. Therefore, effective and efficient receivables management is crucial for Persada Hospital to achieve its insurance receivables settlement targets. Method: The research employs a qualitative descriptive method with source triangulation and methods including direct observations and in-depth interviews. Result: Various factors influencing patient receivables with insurance providers include complex insurance policies, slow hospital administrative processes, and delayed payments from insurance companies. Regarding payment measurement, factors such as the number of days from claim submission to payment, percentage of claims paid on time, and number of claims delayed or denied are crucial for evaluating billing process performance. Strategies such as implementing information technology systems, staff training, and enhancing communication with insurance companies can help improve billing performance at hospitals. Conclusion: To continually develop more efficient and transparent billing systems and procedures, standardizing insurance claim procedures, utilizing information technology systems, and enhancing communication and coordination with insurance companies are strategic steps that can enhance the effectiveness and efficiency of patient receivables management.